2020
DOI: 10.3390/fluids5030145
|View full text |Cite
|
Sign up to set email alerts
|

Altimetry-Based Diagnosis of Deep-Reaching Sub-Mesoscale Ocean Fronts

Abstract: Recent studies demonstrate that energetic sub-mesoscale fronts (10–50 km width) extend in the ocean interior, driving large vertical velocities and associated fluxes. However, diagnosing the dynamics of these deep-reaching fronts from in situ observations remains challenging because of the lack of information on the 3-D structure of the horizontal velocity. Here, a realistic numerical simulation in the Antarctic Circumpolar Current (ACC) is used to study the dynamics of submesocale fronts in relation to veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Meanwhile, the ocean surface has been observed at high temporal and spatial resolution with satellites since the early 1990s. Remote sensing allows us to observe surface signa-E. Pauthenet et al: Ocean Stratification network ture of mesoscale to submesoscale features (Siegelman et al, 2020b) and to track climatic trends of sea surface height (Nerem et al, 2018), temperature (Merchant et al, 2019) and salinity (Reul et al, 2020). It is therefore highly valuable for combining sparse in situ profiles and high-resolution remote sensing observations in order to predict the ocean stratification at higher resolution and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the ocean surface has been observed at high temporal and spatial resolution with satellites since the early 1990s. Remote sensing allows us to observe surface signa-E. Pauthenet et al: Ocean Stratification network ture of mesoscale to submesoscale features (Siegelman et al, 2020b) and to track climatic trends of sea surface height (Nerem et al, 2018), temperature (Merchant et al, 2019) and salinity (Reul et al, 2020). It is therefore highly valuable for combining sparse in situ profiles and high-resolution remote sensing observations in order to predict the ocean stratification at higher resolution and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The FSLE from AVISO product are derived with δ 0 = 0.02° and δ f = 0.6°, which is half of one grid point and about the local first Rossby radius, respectively. As such, the FSLE from AVISO have been employed to delineate submesoscale structures (Meunier & LaCasce, 2021;Siegelman et al, 2020). Previous studies have suggested that regions with large FSLE mainly correspond to the regions where submesoscale transports are strong while regions with small FSLE are located in the regions of weak currents (Calil & Richards, 2010;Guo et al, 2019).…”
Section: Satellite Productsmentioning
confidence: 99%
“…Ferrari and Wunsch 2009;McWilliams, 2016;Rocha et al, 2016a). Additionally, they play a critical role in connecting the surface ocean with the interior, through the modulation of the mixed layer seasonality and heat transfer (Capet et al, 2008;Klein et al, 2008;Thomas et al, 2008;Su et al, 2020;Siegelman, 2020). on the location and season, the energy and SSH signature associated with unbalanced motions (including near-inertial flows, internal tides, and inertia-gravity waves) can overcome that of the balanced motions at smaller scales (Rocha et al, 2016b;Qiu et al, 2018, Chereskin et al, 50 2019), imposing a wavelength boundary beyond which SSH measurements provided by satellite altimetry can no longer be used to infer upper ocean geostrophic flows.…”
Section: Introductionmentioning
confidence: 99%